2021
DOI: 10.1111/jdi.13546
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes management by either telemedicine or clinic visit improved glycemic control during the coronavirus disease 2019 pandemic state of emergency in Japan

Abstract: The purpose of this retrospective cohort study at a Tokyo diabetes clinic was to evaluate the effect of telemedicine and clinic visit on glycated hemoglobin (HbA1c) during the coronavirus disease 2019 state of emergency. The effect of telemedicine and clinic visit during the emergency period on the post‐emergency measured HbA1c was evaluated by multiple regression models and logistic regression models adjusted for age, sex, type of diabetes, pre‐emergency HbA1c and body mass index, and body mass index change d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 18 publications
1
32
0
2
Order By: Relevance
“…A switch to remote consultations, delivered either via phone or video calls, during strict lockdowns has been linked with reduced HbA1c. 18 Similarly, pairing flash glucose monitoring with remote control has shown promising outcomes. 19 However, discrepancies among healthcare systems across countries must be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…A switch to remote consultations, delivered either via phone or video calls, during strict lockdowns has been linked with reduced HbA1c. 18 Similarly, pairing flash glucose monitoring with remote control has shown promising outcomes. 19 However, discrepancies among healthcare systems across countries must be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent meta-analysis by Correia and colleagues, 36 which focused on telemedicine interventions implemented in low- and middle-income countries, indicated that telemedicine interventions were effective for diabetes management and resulted in significant reductions in HbA1c levels (standardized mean differences = −0.38, 95% CI = −0.52 to −0.23). In a study from Japan, Onishi and colleagues 39 reported that among patients with diabetes having HbA1c ⩾ 7% before the pandemic outbreak, providing diabetes care through telemedicine during the state of emergency resulted in an improvement to HbA1c < 7% after the emergency period in Japan. In addition to the clinical benefit, the patients on telecare also reported feeling more secure and more care, and the telecare helped the patients and their families take more active roles in their diabetes self-care management.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Before the pandemic, many studies indicated the clinical effectiveness of telemedicine in diabetes care, including significant and clinically relevant reductions in HbA1c. [31][32][33][34][35][36][37][38] Moreover, during the COVID-19 pandemic, two studies from Japan 39 and Saudi Arabia 40 reported similar positive clinical outcomes in terms of glycemic control. In addition, it has been shown that increasing patient contact through frequent phone calls improves patient therapy adherence, motivation, and metabolic control.…”
Section: Introductionmentioning
confidence: 99%
“…Adoption of telemedicine visits may improve outcomes in diabetic patients; retrospective data during the COVID-19 pandemic in 2727 Japanese diabetes patients showed both telemedicine and clinic visits improved glucose control (13). However, in a report of 28,977 patient visits over 2.5 years at a single US center, the odds of completing a visit via telemedicine were lower among non-English speaking and Medicaid insured pediatric patients.…”
Section: Discussionmentioning
confidence: 99%